The invention of black Brazil: black intellectuals and culture production in the post-abolition (PerCursos, 2024)
The article analyzes a revue play produced and staged in 1926 as an instrument for discussing the presence and production of black intellectuals in the post-abolition cultural field. In a political context in which the relationship between race and nation in Brazil was being intensely discussed, the conductor Duque Bicalho and the journalist José Eutrópio – from different perspectives and with different intentions – took an (imprecise, fluid and elastic) notion of black culture as a mark of national identity and Brazilianness. Thus, they looked to cultural manifestations of black – and, in some cases, African – origin as the Brazilian nationality. In this sense, the article studies the strategies adopted by two black intellectuals who turned their attention to discussing the place of black culture in the construction of the nation in Brazil and, consequently, the debate surrounding the access of black people to political rights and citizenship status in the post-abolition period.
Keywords: black intellectuals; race; national identities; post-abolition